Urogenital Pain : A Clinicians Guide to Diagnosis and Interventional Treatments - Sabia, Michael; Sehdev, Jasjit; Bentley, William (Springer International Publishing : Imprint: Springer, 2017)
This book provides an up to date, comprehensive, review of the common urogenital painful conditions. It will serve as a valuable resource for clinicians, urologists, surgeons, gynecologists, palliative care physicians, and many other medical providers. The book reviews presenting signs and symptoms, diagnostic workup, differential diagnoses, interventional treatments, and alternative medical therapy for painful conditions that occur in the urogenital region. The text also provides a clear understanding of how pain is transmitted along with what patient populations are at increased risk in suffering these conditions. The risks, benefits, and indications are discussed in detail for the variety of interventional injections that are available to help manage these conditions.
Keywords: Medicine.; Gynecology.; Pain medicine.; Urology.; elektronické knihy; electronic books